P110/O18 Epigenetic changes by inhibition of DOT1L affect wnt signaling, proliferation and cell cycle in dermal fibroblasts, with no overall effect on collagen deposition in models of fibrosis. (March 2019) - Berghen, N; Cremer, J; De Langhe, E; Lories, R
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: The role of epigenetic factors in the pathophysiology of fibrosis, a hallmark of Systemic Sclerosis, is increasingly explored. DOT1L, the unique H3K79-methyltransferase, methylates histone 3 at the Lysine residue at position 79, thereby regulating gene expression programs. In cartilage and bone, DOT1L has cell-type specific effects on Wnt signaling, a pathway suggested to play an important role in fibrosis. Objectives: To study the role of DOT1L in fibrosis. Methods: Primary human dermal fibroblasts were treated with DOT1L-inhibitor EPZ-5676 or vehicle and stimulated with TGF-β. Expression of smooth muscle alpha 2 actin (ACTA2) and Wnt target genes was measured by RT-qPCR. Western Blot was done for dimethylated H3K79 and β-catenin. Picrosirius Red staining measured collagen deposition. 5-Bromo-2'-deoxy-uridine (BrdU) labeling for proliferation and flow cytometry with Propidium Iodide for cell cycle analysis was done. Col1a2;Cre-ERT 2 ;DOT1l fl/fl mice, injected with tamoxifen to induce a fibroblast-specific DOT1L knockout, were injected subcutaneously with bleomycin or vehicle. Injected skin was analyzed by OH-prolin assay and by histology. Results: The DOT1L-inhibitor EPZ-5676 reduced H3K79 dimethylation in all samples. In breast dermal fibroblasts, the induction of ACTA2 with TGF-β was reduced with DOT1L inhibition, while in abdominal dermal fibroblasts this induction was more pronounced. After 48 hours of TGF-β, collagen deposition was higher in DOT1L-inhibited fibroblasts. After 72 hours of TGF-β however, this deposition was comparable with controls. DOT1L inhibition induced canonical Wnt signaling in fibroblasts, with a small increase in active β-catenin and expression of Lymphoid enhancer-binding factor 1 (LEF1). With DOT1L inhibition, more proliferation of fibroblasts, but also proportionally more cells in the G1/G0 phase and less cells in S and M/G2 phase were seen. In vivo, subcutaneous bleomycin increased murine dermal thickness and skin collagen content. No difference was observed between wild type and mice with a fibroblast-specific deletion of DOT1L. Conclusions: In an in vitro model of fibrosis, ACTA2 induction in DOT1L-inhibited human dermal fibroblasts was dependent on the fibroblast origin. DOT1L inhibition resulted in an earlier deposition of collagen, without differences in deposition at the end points. Inhibition of DOT1L induced canonical Wnt signaling and proliferation but also led to a higher proportion of cells in the G0/G1 phase. In an in vivo murine model of skin fibrosis, no difference in bleomycin-induced skin thickness and collagen content was found when the DOT1L gene was deleted in fibroblasts. Disclosure of Interest: None declared.